Classes de risco ambiental em propriedades rurais agroecológicas no município de Realeza–PR - Grisa , Kleitson Telmo (2022)
This study has as a research element the questions related to the current use of the soil and the search for its ideal use in rural properties that operate in the organic production system. The aim of this study was to analyze the environmental sustainability of agroecological production properties based on environmental risk classes, agricultural aptitude and the way in which the soil is used and occupied by organic producers who are partners of Empresa Biorgânica – Realeza-PR. The operationalization of the research was developed from the specific objectives that consist of characterizing the region of Realeza - PR according to the class of environmental risks and aptitude for the production of family agriculture; analyze the agroecological production properties according to the classes of environmental risks, agricultural skills and their impacts on productivity and identify ways and possibilities of soil use based on the class of environmental risks for safer organic production. The studies carried out addressed the determination of the environmental risk class based on the analysis of relief, flood risk, stoniness, effective soil depth, texture, hydromorphism and drainage, then the agricultural suitability classes were determined, in short, five were analyzed rural properties in the municipality of Realeza - PR in their geographic location, climate, vegetation and soil and, subsequently, mapping of environmental risks, agricultural skills, current soil use and ideal soil use were carried out, the results were also statistically represented after analysis of the maps and the collection questionnaire that was applied to the owners of the analyzed lands. Comparing the results with the literature review research carried out allowed identifying the real possibilities of producing organic agriculture and possible incompatibilities in the use of these techniques and the need to recompose the riparian forest in the southwest region of the State of Paraná.